RELATIONSHIP DOPPLER CEREBROPLACENTAL AS A PREDICTOR OF ADVERSE PERINATAL OUTCOMES IN HIGH RISK PREGNANCIES - Urviola Laura, Richard (2015)
OBJECTIVES: To evaluate the usefulness and predictive capacity cerebroplacentaria ratio (CPR) as a diagnostic test for adverse perinatal outcomes (RPA) in high-risk pregnant women. DESIGN: A prospective longitudinal study with pulsed Doppler velocimetry in fetal umbilical and cerebral arteries was performed. MATERIALS AND METHODS: 72 pregnant women at high risk were selected, between 28 and 41 weeks, excluding patients with multiple pregnancy and fetal congenital anomaly. At all rates of resistance (IR) of the umbilical artery (AU) and fetal middle cerebral artery (MCA) was determined and placental brain relationship is the ratio of IR ACM / IR AU, regarded as abnormal value was calculated = <1. The perinatal outcomes were categorized and correlated with previous rates Doppler. RESULTS: The incidence of RPA was 59.7%. ACM flow was abnormal in 25%, 38.9% AU RCP abnormal finding in 51.4% of the total. In the group with CPR = <1, he found highly significant (p <0.01) increased risk of preterm birth <34 weeks. IUGR, low birth weight and significantly (p <0.05) early neonatal acidosis, mainly. RCP abnormal achieved greater accuracy (88.9%), with positive predictive value of 97.3% compared with IR abnormal AU and ACM alone, which reached 68.1% and 57% in predictive accuracy, respectively. CONCLUSIONS: The abnormal cerebroplacentaria relationship has high predictive of adverse perinatal outcomes in high-risk pregnant women, being more sensitive than the resistance indices of umbilical and middle cerebral arteries, individually.